2009
DOI: 10.1093/nar/gkp952
|View full text |Cite
|
Sign up to set email alerts
|

WormBase: a comprehensive resource for nematode research

Abstract: WormBase (http://www.wormbase.org) is a central data repository for nematode biology. Initially created as a service to the Caenorhabditis elegans research field, WormBase has evolved into a powerful research tool in its own right. In the past 2 years, we expanded WormBase to include the complete genomic sequence, gene predictions and orthology assignments from a range of related nematodes. This comparative data enrich the C. elegans data with improved gene predictions and a better understanding of gene functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
353
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 343 publications
(355 citation statements)
references
References 21 publications
2
353
0
Order By: Relevance
“…c Data from microarray studies as reported in WormBase (Harris et al 2010). d The fecundity 6 SEM of hc198; spe-27 mutant worms transformed with the wild-type copy of the gene.…”
Section: Resultsmentioning
confidence: 99%
“…c Data from microarray studies as reported in WormBase (Harris et al 2010). d The fecundity 6 SEM of hc198; spe-27 mutant worms transformed with the wild-type copy of the gene.…”
Section: Resultsmentioning
confidence: 99%
“…(A) Scale drawing of UNC--16 showing the location of nonsense mutations isolated in this study, conserved regions, and regions known to interact with other proteins from previous studies of UNC--16 and its JIP3 orthologs. Percentages refer to percent identities when comparing the indicated regions of UNC--16 (ZK1098.10b.1 from www.wormbase.org; freeze WS200; (HARRIS et al 2009) to its human JIP3 ortholog (NP_003962). References for interaction sites are as follows: KHC (Kinesin Heavy Chain) ; JNK (c--Jun N--terminal kinase) , KLC (Kinesin Light Chain) .…”
Section: Figure S1mentioning
confidence: 99%
“…Next, we compared the list of signalogs and their predicted pathway memberships to pathway annotations found in pathway databases, as well as the list of ortholog predictions to previously published interolog predictions. To assess the novelty of signalogs and quantify the confidence level of each prediction, we performed semiautomated searches using PubMed, UniProt, GO, Wormbase, FlyBase, iHOP, and Chilibot web services [15,18,[29][30][31][32]. During this process, direct manual curation and Python scripts checking multiple proteins in one webservice were used.…”
Section: Defining the Novelty Of Signaling Protein Predictions Basedmentioning
confidence: 99%